2019 IEEE 21st Conference on Business Informatics (CBI) 2019
DOI: 10.1109/cbi.2019.00047
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Task-Technology Fit in Public Administration and Management: A Configurational Approach

Abstract: In spite of heavy investments in digital technologies in the public sector over the past couple of decades, one of the most important issues regarding the value realized from them is that in many cases he technologies used to support tasks of professionals are often not used as intended, or even not used at all. Apart from not perceiving any positive impacts, several studies have noted negative effects when professionals incorporate different novel technologies into their work tasks. Building the task-technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The TTF model consists of the four major constructs: technology characteristics, task characteristics, TTF, and technology utilization (Strong et al , 2006). It has been tested extensively, and it has been shown that TTF affects both usage and performance of individuals as well as organizational outcomes (Cady et al , 2014; Furneaux, 2012; Gebauer et al , 2010; Hsiao and Chen, 2012; Mikalef and Torvatn, 2019a, b; Mikalef et al , 2019; Zhang et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The TTF model consists of the four major constructs: technology characteristics, task characteristics, TTF, and technology utilization (Strong et al , 2006). It has been tested extensively, and it has been shown that TTF affects both usage and performance of individuals as well as organizational outcomes (Cady et al , 2014; Furneaux, 2012; Gebauer et al , 2010; Hsiao and Chen, 2012; Mikalef and Torvatn, 2019a, b; Mikalef et al , 2019; Zhang et al , 2011).…”
Section: Introductionmentioning
confidence: 99%